A Dynamic Compensation Scheme for Multi-Load WPT System Based on Parity-Time Symmetry - Yan Liu; Jiaming Wei; Minghui Han (IEEE Access)
In multi-load wireless power transfer (WPT) systems, it is a challenging problem to ensure that each load obtains constant output power and maintains high efficiency when the coupling conditions change or the resonant frequencies of the loads are different. This paper proposes a dynamic compensation scheme for the multi-load parity-time symmetric wireless power transmission (PT-WPT) system. First, based on the analysis of the multi-load PT-WPT circuit model, a switch capacitor circuit (SCC) is proposed to replace the traditional compensation capacitor. The SCC consists of capacitors and transistors, which can dynamically adjust the equivalent capacitance by changing the conduction angle to make the system work in resonance and adapt to different frequency multi-load conditions. Secondly, to calculate the SCC conduction angle more accurately in the case of multi-coil cross-coupling. A dynamic compensation control strategy is proposed based on model predictive control (MPC). The system state is predicted by detecting the phase difference between the transmitter voltage and current, and the SCC is controlled to generate the appropriate equivalent capacitance for rapid dynamic compensation. Finally, an experimental prototype of the 50 W dual-load PT-WPT system was fabricated. The experimental results show that when the system supplies loads with resonant frequencies of 150 kHz and 200 kHz simultaneously, the transmission efficiency of the system is improved from 87% to 90.8% by using MPC dynamic predictive control. The system can maintain transmission efficiency of 90% or above within a certain transmission distance.